2018
DOI: 10.1080/08856257.2018.1553137
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ expectations of children with Down Syndrome starting school in the United Arab Emirates or United Kingdom

Abstract: The aim of the Leeds Beckett Repository is to provide open access to our research, as required by funder policies and permitted by publishers and copyright law.The Leeds Beckett repository holds a wide range of publications, each of which has been checked for copyright and the relevant embargo period has been applied by the Research Services team.We operate on a standard take-down policy. If you are the author or publisher of an output and you would like it removed from the repository, please contact us and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Historically, research on factors that shape teacher expectations has focused on the perspective that there are qualities about students that lead teachers to form different expectations for individual students (Wang et al, 2018). However, in more recent years, researchers have considered factors at the teacher‐level that can shape the expectations they form of students (Takriti et al, 2019). Three of the retrieved articles focused on different teacher‐related factors that shaped the expectations teachers held for students in the early grades.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Historically, research on factors that shape teacher expectations has focused on the perspective that there are qualities about students that lead teachers to form different expectations for individual students (Wang et al, 2018). However, in more recent years, researchers have considered factors at the teacher‐level that can shape the expectations they form of students (Takriti et al, 2019). Three of the retrieved articles focused on different teacher‐related factors that shaped the expectations teachers held for students in the early grades.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to regional or cultural differences, Takriti et al (2019) investigated the perspectives of kindergarten and grade one teachers in the UK compared to those in the UAE related to the early school success of students with special education needs. Teachers in both countries rated items related to social adjustment and disposition (e.g., being keen to go to school, having friends) as holding the highest importance for a successful transition into school.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ring et al (2016) found that teachers placed great emphasis on children being socially and emotionally ready for school, being able to follow routines, being independent and, crucially, having good communication skills. Similarly, studies of teacher expectations in the UAE revealed a similar pattern of importance being placed on new starters being emotionally mature (Takriti, Elhoweris & Atkinson, 2018;Takriti, Atkinson & Elhoweris, 2019;Takriti, 2019;Atkinson, Takriti & Elhoweris, 2020). Parker and Neuharth-Pritchett (2006) and O'Kane and Hayes (2013) found that teachers perceived that early years' provision is becoming more academic and there is a need to focus more on academic skills alongside social competence.…”
Section: Sub-theme 2: Talking Is a Successful Transitionmentioning
confidence: 90%